Math, asked by arnavagupta3006, 1 year ago

please answer correctly

Attachments:

Answers

Answered by sharonwilson2006
0

Answer:

ans=1

Step-by-step explanation:

hope u find it helpful

Answered by venkatavineela3
0

Answer:

Step-by-step explanation:

x=sqrt(3)+sqrt(2)/sqrt(3)-sqrt(2)

rationalise the denominator by sqrt(3)+sqrtr(2)

x=(sqrt(3)+sqrt(2))^2/1

=3+2+2sqrt(6)

=5+2sqrt(6)

1/x=1/5+2sqrt(6)

rationalise the denominator

=5-2sqrt(6)/1

=5-2sqrt(6)

x^2=25+24+20sqrt(6)

1/x^2=25+24-20sqrt(6)

x^2+1/x^2=98

Similar questions